Purchasing power parity in transition countries: Panel stationary test with smooth and sharp breaks - Mohsen Bahmani-Oskooee; Tsangyao Chang; Tsung-Pao Wu (International Journal of Financial Studies, 2015)
This study examines whether the long-run purchasing power parity (PPP) holds in transition economies (Bulgaria, the Czech Republic, Hungary, Latvia, Lithuania, Poland, Romania and Russia) using monthly data over the 1995 - 2011 period. We apply a recently introduced panel stationary test, which accounts for sharp breaks and smooth shifts. The results indicate that the PPP holds only in two countries (i.e., Lithuania and Poland).
Keywords: C22; F31; 330; purchasing power parity; transition countries; panel stationary test; sharp breaks and smooth breaks; Fourier function